Analysis of Enterprise Resource Planning (ERP) Systems Implementation - Marti Widya Sari; Banu Santoso; Adhi Wibowo (Journal of Telematics and Informatics, 2018)
This research discussed about ERP system success in its post-implementation, therefore, it can only be applied to organisations that have implemented an ERP system. To achieve the research objective, a rigorous strategy for searching the literature was developed. The current study selected supporting ERP references, including theories, research, frameworks, and other verified information resources. The target of population is the ERP end user, specifically, a user who works in a company that has implemented an ERP system.  The sample was composed of various industry types that have implemented ERP systems, and the count of respondents is 60. The result of this research shows the measurement of system quality, service quality, information quality, perceived usefulness, user satisfaction and benefit of ERP system.